(untitled) (Philological Studies, 2025)
The aforementioned work provides a review of the Macedonian question in relation to the Russian "Macedonian Expedition", led by the academician N.P. Kondakov, its journey through Macedonia in the run-up to the Ilinden Uprising, the divisions and insights that emerged from it, which had a profound impact on the events in the Balkans in the period during and after the collapse of the Ottoman Empire. The subject of analysis is the correspondence and insights of the members of this scientific expedition, including the linguist and Slavist P. A. Lavrov and the historian P.N. Miljukov, related to the geopolitical situation on the Balkan Peninsula and the position of the Macedonian population in that period. This expedition is also significant because of the meeting of Krste P. Misirkov with P.A. Lavrov, who would later become his mentor and supporter in his research on Macedonian dialects, language, identity and culture. In addition to the paper, there is a selection of photo materials from this expedition, part of the archival collection of the Institute of Folklore "Marko Cepenkov" - Skopje, which speak of the exceptional significance that this scientific expedition has in historiographical, Byzantine, Slavic, Macedonian, archaeological and linguistic research, as well as for the historical continuity of the "Ohrid Archbishopric" and its sacral relics.